2014
DOI: 10.1177/2047487313519346
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and cardiovascular disease risk reclassification: Findings from NHANES III

Abstract: sUA was not an independent predictor of both CVD and CHD mortality. Ethnicity did not influence the association of sUA with CVD mortality. Furthermore, sUA did not add to risk assessment beyond traditional CVD risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 27 publications
1
71
0
5
Order By: Relevance
“…After screening the title or abstract, 1028 studies were excluded, and the remaining 59 were further identified by reading the full-text. According to the predefined inclusion criteria, 14 studies [2134] enrolling 341 389 participants were included in the meta-analysis. Based on the reference lists of the included studies, we retrieved six potential studies, but none met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the title or abstract, 1028 studies were excluded, and the remaining 59 were further identified by reading the full-text. According to the predefined inclusion criteria, 14 studies [2134] enrolling 341 389 participants were included in the meta-analysis. Based on the reference lists of the included studies, we retrieved six potential studies, but none met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 included studies, four were performed in the United States [21, 22, 29, 34], five in Europe [24, 26, 30, 31, 33] and five in Asia [22, 25, 27, 28, 32]. All except one [24] were written in English.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 A recent publication based on NHANES III data demonstrated modest evidence of a J-shaped relationship between uric acid level and CVD mortality in a population limited to those without a history of diabetes or CVD. 24 Investigators have suggested that this inverted association may be due to the protective role of uric acid as an antioxidant. 21,23 It has also been suggested that low uric acid levels may reflect persons with poor nutritional status or wasting, although in the present study persons with lower uric acid have more optimal levels of measured health characteristics compared with persons with higher uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…9,32 Some studies have suggested that hyperuricemia is also an independent predictor for cardiovascular disease, 10,11 whereas others have not. 33 Researchers have suggested that hyperuricemia might elevate cardiovascular disease risk indirectly by increasing the risk of hypertension. 34 Several studies suggest that hyperuricemia is a stronger predictor of future disease in women, who have lower serum uric acid concentrations than men.…”
Section: Discussionmentioning
confidence: 99%